ANALISIS PENGARUH KEMIRINGAN JALAN ANGKUT TERHADAP KONSUMSI BAHAN BAKAR DUMP TRUCK HINO 500 FG 235 JJ - Rinaldi R. Wincono; Juanita R. Horman (INTAN Jurnal Penelitian Tambang, 2019)
Dump truck is one of the mechanical equipment that become the main conveyance in mining activity especially in open pit. In its use dump trucks require a variety of operational needs, one of them the need for fuel oil (diesel). Transportation Activities conducted by PT. Sumber Anugrah Buana using Hino 500 FG 235 JJ type hauling equipment. Transportation distance from the mining front to the stockyard of 120 meters is divided into two segments, segment A-B and B`-C with each slope of 10% -20%. The average fuel consumption of Hino 500 FG 235 JJ is 7.11 liter / hour. Based on the results of the analysis is known that the slope of the haul road greatly affect the large consumption of diesel fuel. Fuel consumption is most needed when traversing an uphill road with a 30% (+) road slope. On the uphill road there are several forces as a vehicle inhibitor.